Searching for modernization: Entrepreneurship education, economic growth, outmigration and the need for change in rural Nova Scotia, Canada - Hadley, Gregory (Journal of Interdisciplinary Studies in Education, 2024)
This paper considers the theoretical underpinnings of rural out-migration and economic stagnation, specific to rural Nova Scotia, Canada, and argues that rural Nova Scotia has, in part, misapplied the tenets of modernization.  It situates out-migration, and economic stagnation, amongst Modernization Theory and considers how economic rejuvenation, vis a vis entrepreneurship education, can, potentially, revivify the topophilic bonds between person and (rural) community. Structurally, this paper argues three points: first, that rural Nova Scotia is enduring a misapplication of modernization, resulting in a lingering traditionalism that pushes people out and dampens economic growth. Second, that rural Nova Scotia would benefit from a structural shift in its economic model and third, that community economic development through entrepreneurship stands a reasonable chance of reserving the social and economic misfortune now ubiquitous in the areas outside of Nova Scotia’s capital region.